2017
DOI: 10.1002/cbdv.201700158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Factors on Essential Oil Variability in Origanum compactum Benth. Growing Wild in Morocco

Abstract: The present study aimed to evaluate the influence of environmental factors on essential oils (EOs) composition of Origanum compactum populations sampled all over the distribution area of the species in Morocco, and to determine the extent of the chemical profiles throughout the geographical distribution of the species. The chemical compositions were submitted to canonical correlation analysis and canonical discriminant analysis that indicated a significant relationship between oil components and some environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 46 publications
4
40
2
2
Order By: Relevance
“…They have been used for centuries not only in different fields/branches of industry but also in ethnobotanical medicine [1]. The quantitative and qualitative composition of these compounds is determined by different factors, e.g., plant origin and habitat [2,3], cultivar [4,5], plant development phase [4,6,7], seasonal variations [8,9], weather and Studies have indicated that the dominant EO components in the flower heads of A. chamissonis are similar to those found in A. montana [6,17,39], including molecules with significance emphasized and confirmed in the literature. The main EO component of A. chamissonis is alpha-pinene exhibiting antioxidative, anti-inflammatory, antimicrobial, and antiparasitic bioactivity [17,[40][41][42][43] as well as a significant effect on the inhibition of tumor invasion [44].…”
Section: Introductionmentioning
confidence: 99%
“…They have been used for centuries not only in different fields/branches of industry but also in ethnobotanical medicine [1]. The quantitative and qualitative composition of these compounds is determined by different factors, e.g., plant origin and habitat [2,3], cultivar [4,5], plant development phase [4,6,7], seasonal variations [8,9], weather and Studies have indicated that the dominant EO components in the flower heads of A. chamissonis are similar to those found in A. montana [6,17,39], including molecules with significance emphasized and confirmed in the literature. The main EO component of A. chamissonis is alpha-pinene exhibiting antioxidative, anti-inflammatory, antimicrobial, and antiparasitic bioactivity [17,[40][41][42][43] as well as a significant effect on the inhibition of tumor invasion [44].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the chemical constituents identified in this study have been reported in L. scoparium essential oil albeit at different quantities [9,13,16,35,36]. These differences are expected because the chemical composition of essential oils is known to vary by plant geographic origin, stage of development, growing conditions, developmental stage of the plant, method of extraction, solvent used for extraction, and photosensitivity of some compounds in the extract [36][37][38].…”
Section: Discussionmentioning
confidence: 84%
“…The differences in the chemical composition of the same species are probably due to various parameters, including the environment, geographic origin, and harvest period (Aboukhalid et al 2017;Yeddes et al 2018).…”
Section: Discussionmentioning
confidence: 99%